Clinical application of gelatin sponge microparticles-transcatheter arterial chemoembolization combined with synchronous antigen-presenting dendritic cell sequential reinfusion for treatment of advanced large liver cancer: A single-center, prospective, non-randomized, controlled trial. Issue 8 (25th February 2022) - Zhao, Guang Sheng; Liu, Song; Liu, Ying; Li, Chuang; Wang, Ruo Yu; Bian, Jie; Zhu, Rui Ping; Zhou, Jun; Zhang, Yue Wei
Abstract : Abstract: To assess the clinical efficacy and safety of gelatin sponge microparticles-transcatheter arterial chemoembolization (GSMs-TACE) plus synchronous antigen-presenting dendritic cell (DC) sequential reinfusion for advanced large liver cancer (LC). Patients with large LC were assigned to the experimental (combined sequential DC therapy) or control group. All patients received standardized GSMs-TACE. In the experimental group, 60 mL of peripheral blood was collected for in vitro culture of DCs (10–14 days). Then, intravenous reinfusion was conducted 3 times within 10, 20, and 30 days after surgery. Adverse reactions during the treatment were recorded and evaluated. The overall survival, transcatheter arterial chemoembolization frequency, and physical score (PS) were calculated. The median survival time of the experimental group was significantly longer than that of the control group. There were significant differences in median progression-free survival between the 2 groups ( P  < .05) and the objective effective rate at 1 and 6 months and 1 year ( P  < .05), but not 2 years ( P  > .05). The PSs of 2 groups were significantly improved at 1 month after GSMs-TACE, with more obvious improvement in the experimental group ( P  < .05). GSMs-TACE plus synchronous DC sequential reinfusion significantly prolonged the median survival time, improved the tumor response rate and PS, prolonged progression-free survival, and reduced intervention frequency. GSMs-TACE plus synchronous DC sequential reinfusion treatment is suitable for comprehensive treatment of patients with advanced larger LC in China.